Biomechanical analysis of the breaststroke start - Seifert, L.; Vantorre, J.; Chollet, D. (International Journal of Sports Medicine, 2007)
The aim of this study was to analyse the kinematics and coordination of the breaststroke start as regards to skill level using a video device. Ten national swimmers were compared with an international swimmer. All swimmers simulated the 100-m pace for 25 m after a grab start. The kinematical analysis assessed the durations of leave block, flight, entry and glide, pull-out, and the swim up to the 15-m mark phases. The coordination analysis assessed the durations of the time spent with the arms close to the thighs after a complete arm pull-push, the time gap between the end of the arm recovery and the beginning of the leg propulsion during the pull-out phase and at the first swim stroke, and the time gap between the end of leg propulsion and the beginning of arm propulsion. The international swimmer had a shorter 15-m start time than the national swimmers due to shorter times in the swim phase, longer times in the underwater phase, longer times spent with the arms close to the thighs and in glide with the body in extension. The whole population showed a negative superposition of leg propulsion with arm recovery at the pull-out phase, which disappeared at the first swim stroke.